Linear Transformation Trace
📂Linear Algebra Linear Transformation Trace Definition Let V V V be a n n n -dimensional vector space . Let f : V → V f : V \to V f : V → V be a linear transformation . Let B = { e i } B = \left\{ e_{i} \right\} B = { e i } be a basis of V V V . Let n × n n \times n n × n matrix A A A be the matrix representation of f f f with respect to B B B .
A = [ f ] B
A = [f]_{B}
A = [ f ] B
Since f ( e i ) ∈ V f(e_{i}) \in V f ( e i ) ∈ V , we represent it as f ( e i ) = ∑ f j ( e i ) e j f(e_{i}) = \sum f_{j}(e_{i})e_{j} f ( e i ) = ∑ f j ( e i ) e j . Then,
A = [ f 1 ( e 1 ) f 2 ( e 1 ) ⋯ f n ( e 1 ) f 1 ( e 2 ) f 2 ( e 2 ) ⋯ f n ( e 2 ) ⋮ ⋮ ⋱ ⋮ f 1 ( e n ) f 2 ( e n ) ⋯ f n ( e n ) ]
A = \begin{bmatrix} f_{1}(e_{1}) & f_{2}(e_{1}) & \cdots & f_{n}(e_{1}) \\ f_{1}(e_{2}) & f_{2}(e_{2}) & \cdots & f_{n}(e_{2}) \\ \vdots & \vdots & \ddots & \vdots \\ f_{1}(e_{n}) & f_{2}(e_{n}) & \cdots & f_{n}(e_{n}) \end{bmatrix}
A = f 1 ( e 1 ) f 1 ( e 2 ) ⋮ f 1 ( e n ) f 2 ( e 1 ) f 2 ( e 2 ) ⋮ f 2 ( e n ) ⋯ ⋯ ⋱ ⋯ f n ( e 1 ) f n ( e 2 ) ⋮ f n ( e n )
Define the trace of the linear transformation f f f , tr f \tr f tr f , as follows:
tr f : = tr ( A ) = ∑ i f i ( e i )
\tr f := \tr(A) = \sum_{i} f_{i}(e_{i})
tr f := tr ( A ) = i ∑ f i ( e i )
Here, tr ( A ) \tr(A) tr ( A ) is the trace of matrix A A A .
Explanation Since there exists a corresponding matrix for a linear transformation, the trace of the linear transformation can be naturally defined.
Basis Invariance The trace of a linear transformation does not depend on the choice of basis. By the definition, it might seem that the matrix A A A depends on the basis, so choosing a different basis B ′ B^{\prime} B ′ to obtain matrix A ′ A^{\prime} A ′ would change the value of tr f \tr f tr f . However, the two matrices A A A and A ′ A^{\prime} A ′ are similar . Since the trace is invariant under similarity, tr f \tr f tr f is well defined irrespective of the choice of basis for V V V .
Inner Product Representation tr f \tr f tr f can be expressed using the given metric . Let’s say metric g g g is given. Then,
g ( f ( e i ) , e k ) = g ( f j ( e i ) e j , e k ) = f j ( e i ) g ( e j , e k ) = f j ( e i ) g j k
g(f(e_{i}), e_{k}) = g( f_{j}(e_{i})e_{j}, e_{k} ) = f_{j}(e_{i}) g( e_{j}, e_{k} ) = f_{j}(e_{i})g_{jk}
g ( f ( e i ) , e k ) = g ( f j ( e i ) e j , e k ) = f j ( e i ) g ( e j , e k ) = f j ( e i ) g jk
Multiply both sides by g k l g^{kl} g k l and sum over index k k k ,
g k l g ( f ( e i ) , e k ) = f j ( e i ) g j k g k l = f j ( e i ) δ j l = f l ( e i )
g^{kl} g(f(e_{i}), e_{k}) = f_{j}(e_{i})g_{jk}g^{kl} = f_{j}(e_{i})\delta_{j}^{l} = f_{l}(e_{i})
g k l g ( f ( e i ) , e k ) = f j ( e i ) g jk g k l = f j ( e i ) δ j l = f l ( e i )
Therefore, we obtain the following.
tr f = f i ( e i ) = g ( f ( e i ) , e k ) g k i
\tr f = f_{i}(e_{i}) = g(f(e_{i}), e_{k})g^{ki}
tr f = f i ( e i ) = g ( f ( e i ) , e k ) g ki